The comprehensive impact of pityriasis rubra pilaris on physical symptoms, mental health, and activities of daily living: A mixed methods study. Issue 1 (16th January 2023) - Velasco, Rose C.; Cutler, Brett; McCue, William; Greiling, Teri M.
Abstract: Background: Pityriasis rubra pilaris (PRP) is a rare and often severe inflammatory skin disorder with major detriment to patients' quality of life. While past studies have described in detail the morphologic and histopathologic presentations of PRP, little attention has been given to the patient experience. Objectives: To identify the physical, mental, and daily living impacts of patients living with PRP Methods: Four focus groups involving 47 participants with PRP from six countries were conducted in English. Sessions were recorded and codified by themes, which were used to compose a 23‐question follow‐up survey. Results: Common physical symptoms that impacted a majority of PRP patients included severe pruritus, pain (generalised in involved skin, localised to palmoplantar fissures, and arthralgias), poor sleep, fatigue, anhidrosis, body temperature dysregulation, joint pain, buildup of material in the ears, and rhinorrhea. Participants felt that PRP was associated with a strong negative mental impact that caused depression, anxiety, embarrassment, loneliness, loss of self‐esteem, and memory loss or brain fog. 38% endorsed passive suicidal ideation and 4% active suicidal ideation. Common daily activity impacts included loss of fine motor ability and difficulty walking from palmoplantar keratoderma, difficulty wearing normal clothing, difficulty working, and difficulty leaving the home. Participants reported a mean of six applications of topical creams or ointments daily. Conclusions: This study illustrates the debilitating daily life impacts of PRP in a variety of domains. In addition to care by a dermatologist, patients should be evaluated for the need for referral to ophthalmology, otolaryngology, and podiatry. Patients with PRP felt strongly that the mental health impact of PRP was not given enough attention by providers. Given the high rate of depression, anxiety, and passive and active suicidal ideation, providers should evaluate patients' mental health and offer a referral to psychiatry and other mental health providers.